Adventure time. Volume 8 - North, Ryan 1980-; Hastings, Chris, 1983- (KaBOOM!, 2016)
When everyone in the Land of Ooo wakes up with no knowledge of how to cook, Princess Bubblegum tasks Finn and Jake to get to the bottom of the memory problems.